Pemberdayaan Masyarakat Berbasis Ekonomi Mikro Melalui Peran LazisMu Desa Klumpit, Kudus - Arifa Fadilah, Adiba (Community Development: Jurnal Pengembangan Masyarakat Islam, 2020)
This study aims to determine the role of LAZISMU in micro economic empowerment for the development of business micro in the form of utilizing funds at LAZISMU Muhammadiyah Kudus.  The problem in this research is poverty, which is the condition of the inability of the community to meet basic needs which include economic, education and health needs.  Where this is often felt by families or the middle to lower class society. This study uses a qualitative approach with an intrinsic method.  Primary sources interviews and seconder data from website LAZISMU.  The results showed that, the role of LAZISMU in micro economic empowerment. Poverty alleviation created by LAZISMU is based on a program that has been designed to eradicate poverty by empowering the community so that people can have added value income every month.  So that people have a better economy than before.  Developing the economic potential of families and communities in increasing productivity in an effort to alleviate poverty.  The role of LAZISMU Kudus in the Micro Economy Empowerment Program through the development of Martabak noodle business micro in the village of Klumpit Gebog in the form of business capital assistance providing direct business capital in the form of cash.